State-Owned Bank Health Level using the CAMELS Method for the Period of 2015-2020 - Sutisnawati*, Yayah; Pamungkas, Nurul Putri (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2022)
The purpose of this study was to identify the soundness level of a bank by using CAR, NPL, ROA, BOPO, and long-distance relationships in the CAMELS system in one of the Banking SOEs. The method used is a quantitative method with a descriptive approach over a period of six years (2015-2020). The research findings show a comparison of the 2015-2020 CAR in the face of depreciation and escalation or the occurrence of instability. There was also a decrease in the CAR ratio in 2015-2016 due to an increase in the amount of RWA without being offset by bank capital. Comparison of NPLs in BUMN Banking escalates every year due to the high risk of missing budget formation or bad loans. These results were found by analyzing each level of the soundness of each ratio variable (CAR, NPL, ROA) to financial institutions. Keywords: Banking; Financial; ROA; BOPO; CAR Tujuan penelitian ini untuk mengidentifikasi tingkat kesehatan bank dengan menggunakan Rasio CAR, NPL, ROA, BOPO, dan hubungan jarak jauh dalam sistem CAMELS di salah satu BUMN Perbankan. Metode yang digunakan adalah metode kuantitatif dengan pendekatan deskriptif dalam periode enam tahun (2015-2020). Temuan penelitian menunjukkan perbandingan CAR tahun 2015-2020 dalam menghadapi penyusutan dan eskalasi atau terjadinya instabilitas. Terjadi pula penurunan Rasio CAR tahun 2015-2016 karena peningkatan jumlah ATMR tanpa diimbangi permodalan bank. Perbandingan NPL di BUMN Perbankan tiap tahun terjadi eskalasi karena tingginya resiko pembentukan anggaran yang hilang atau kredit macet. Hasil tersebut ditemukan dengan menganalisis setiap tingkat kesehatan dari setiap variabel rasio (CAR, NPL, ROA) terhadap lembaga keuangan. Kata Kunci: Perbankan; Keuangan; ROA; BOPO; CAR